PENGEMBANGAN PARIWISATA DI RUPAT UTARA DALAM PERSPEKTIF SUSTAINABLE TOURISM - Jesika Puteri; Syafri Harto; Adianto Adianto (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2022)
Abstract The tourism sector plays an important role in supporting the economy, this makes tourist receiving countries competing to develop the tourism industry. Various efforts have been made to make tourist destinations attractive and able to generate as many tourist visits as possible. Researchers want to see the extent of tourism development in North Rupat based on available data in the relevant Office, as well as the extent of realization in the development of North Rupat Island as stated in the 2016-2021 National Tourism Strategic Area Plan, which is targeted this year and whether tourism development has been realized. sustainably. Researchers also want to see and find out what are the inhibiting factors in tourism development in Bengkalis Regency. This research method is qualitative which results in the finding that tourism development in the perspective of Sustainable Tourism in North Rupat, Bengkalis Regency through the application of the nine principles of sustainable tourism in the North Rupat tourism area has not run as a whole.